Digitalization of Business as a Method of Anti-crisis Strategy During the Pandemic ("Journal "U". Economy. Management. Finance.", 2020)
The development and implementation of digitalization in business processes today is one of the key business objectives. This became especially relevant during the pandemic as part of the recovery growth of the economy. The article assumes that digital technologies are one of the promising methods of crisis management during a crisis, including a pandemic.
Keywords: digitalization; digital technologies; anti-crisis management; anti-crisis strategy; pandemic; recovery growth